Primary care consultation behaviours of long-term, adult survivors of cancer in the UK. - Khan, N; Watson, E; Rose, P (2011)
The population of cancer survivors is growing, and GPs have an increasing role in their care. The General Practice Research Database was used to compare consultation rates between cancer survivors and controls. Breast and colorectal cancer survivors had one more consultation per year compared with controls up to 5 years after diagnosis; rates then converged at 10 years post-diagnosis. Prostate cancer survivors consistently consulted up to three more times per year than controls. These increased consultation rates are leading to an impact on service capacity.